Teachers' Professionalism in Improving the Quality of Students' Reading and Memorization of the Qur'an - Wahyudi, Wahyudi; Supriyoko, Supriyoko; Hasyim, Dardiri (Journal of Social Science and Education Research, 2025)
The purpose of this article is to explore teacher professionalism in improving the quality of students' reading and memorization. Teacher professionalism in learning includes pedagogical competence, mastery of effective learning methods, and skills in creating an effective and supportive learning atmosphere. This research identifies the challenges teachers face in teaching the Koran. Through a literature review approach, this research seeks to explore the relationship between teacher professionalism and student learning outcomes. The results of the study show that teachers who have high expertise in their field, and are able to develop approaches that suit the needs of differentiated students, can significantly improve the quality of students' reading and memorization. However, several challenges that teachers often face, such as lack of training competency, limited time and facilities, hinder the teacher's role. This research tries to provide this picture as well as provide recommendations for strengthening teacher professionalism through continuous training and strengthening policies that support more professional and effective teaching of the Koran.